2021
DOI: 10.5530/ijpi.2021.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Nanodrug Delivery Systems in Periodontics

Abstract: Nanotechnology is of intense interest to researchers due to the basic fact that the properties of the material can be effectively manipulated when the size is transformed to nanoscopic. New opportunities arise out of the unique features which have been effectually utilized in the development of nano pharmaceuticals. This has revolutionized the health care system extensively by its diverse applications in modern medicine and dental science. Material science and periodontics have jointly adopted this technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…3 A range of nanoparticles are being utilized for drug delivery in periodontal treatments including nanospheres, nanogels, nanocomposites, nano capsules, nanofibers, dendrimers and liposomes. 3 For example a study done by Lee et al in 2016 showed that Poly-D, L-lactic-coglycolic acid derived nanocarriers loaded with tetracycline and lovastatin demonstrated effectiveness in treating canine models with periodontitis. They found out that it was not only biocompatible but also inhibited bacterial growth in human therapy.…”
Section: Nanoscale Delivery Systemsmentioning
confidence: 99%
“…3 A range of nanoparticles are being utilized for drug delivery in periodontal treatments including nanospheres, nanogels, nanocomposites, nano capsules, nanofibers, dendrimers and liposomes. 3 For example a study done by Lee et al in 2016 showed that Poly-D, L-lactic-coglycolic acid derived nanocarriers loaded with tetracycline and lovastatin demonstrated effectiveness in treating canine models with periodontitis. They found out that it was not only biocompatible but also inhibited bacterial growth in human therapy.…”
Section: Nanoscale Delivery Systemsmentioning
confidence: 99%
“…The literature reviews disclose that preventive dentistry, restorative dentistry, endodontics, implantology, prosthetic dentistry, oral cancers, and periodontology all benefit from NPs ( Fig. 1 ) [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%